Molecular Dynamics Simulations of Selective Metabolite Transport across the Propanediol Bacterial Microcompartment Shell - Park, Jiyong (J Phys Chem B, 2017)
Bacterial microcompartments are giant protein-based organelles that encapsulate special metabolic pathways in diverse bacteria. Structural and genetic studies indicate that metabolic substrates enter these microcompartments by passing through the central pores in hexameric assemblies of shell proteins. Limiting the escape of toxic metabolic intermediates created inside the microcompartments would confer a selective advantage for the host organism. Here, we report the first molecular dynamics (MD) simulation studies to analyze small-molecule transport across a microcompartment shell. PduA is a major shell protein in a bacterial microcompartment that metabolizes 1,2-propanediol via a toxic aldehyde intermediate, propionaldehyde. Using both metadynamics and replica-exchange umbrella sampling, we find that the pore of the PduA hexamer has a lower energy barrier for passage of the propanediol substrate compared to the toxic propionaldehyde generated within the microcompartment. The energetic effect is consistent with a lower capacity of a serine side chain, which protrudes into the pore at a point of constriction, to form hydrogen bonds with propionaldehyde relative to the more freely permeable propanediol. The results highlight the importance of molecular diffusion and transport in a new biological context.